2018
DOI: 10.1089/wound.2017.0766
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diluted Acetylcholine Promotes Wound Repair in an In Vivo Model

Abstract: Objective: Wound healing is a dynamic, interactive, and complex process that involves a series of events, including inflammation, migration, proliferation, granulation tissue formation, and matrix remodeling. Despite the high frequency of serious slow-healing wounds, there is still no adequate therapy. The aim of this study is to evaluate a new highly diluted acetylcholine (Ach) formulation obtained through a sequential kinetic activation (SKA) method applied to a wound healing in vivo model to verify the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Furthermore, donepezil may act differently on bone and skin cells [ 35 , 36 ]. Even though donepezil does not have a local direct effect on osteoprogenitor mesenchymal stem cell (MSCs) [ 37 ], acetylcholine could accelerate keratinocyte proliferation, migration, and viability [ 38 ]. This is mediated through the action of non-neuronal cholinergic receptors; muscarinic (M1 and M3) and a7 nicotinic receptors of keratinocytes [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, donepezil may act differently on bone and skin cells [ 35 , 36 ]. Even though donepezil does not have a local direct effect on osteoprogenitor mesenchymal stem cell (MSCs) [ 37 ], acetylcholine could accelerate keratinocyte proliferation, migration, and viability [ 38 ]. This is mediated through the action of non-neuronal cholinergic receptors; muscarinic (M1 and M3) and a7 nicotinic receptors of keratinocytes [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though donepezil does not have a local direct effect on osteoprogenitor mesenchymal stem cell (MSCs) [ 37 ], acetylcholine could accelerate keratinocyte proliferation, migration, and viability [ 38 ]. This is mediated through the action of non-neuronal cholinergic receptors; muscarinic (M1 and M3) and a7 nicotinic receptors of keratinocytes [ 38 , 39 ]. Moreover, donepezil could further enhance skin wound healing through a feed-back loop, in which keratinocyte activation stimulates fibroblasts to release growth factors, which in turn stimulate keratinocyte proliferation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…2.9. MMP-9 Quantification Assay MMP-9 ELISA Kit (DBA, Italy, CN KA0398) was used to quantify MMP-9 on culture supernatant samples, following the manufacturer's instructions [56]. Briefly, samples in 96-well/plate were incubated at 37 • C for 90 min, and then biotinylated antibody and ABC working solution were added and the plate was incubated at 37 • C for 60 and 30 min, respectively.…”
Section: P53 Activitymentioning
confidence: 99%
“…In this paper, the developed method was used for the study of water protein solutions (interferon-gamma (IFNγ), antibodies to interferon-gamma (Ab to IFNγ)) and glycine buffer (GB) at low concentration. The issue of sensitivity when dealing with low concentrations is of utmost importance, in particular, given the fact that some studies [2][3][4][5][6][7] have revealed the effects observed in protein solutions at low concentrations that can hardly be explained directly by the properties of protein and the solvent, i.e., water. Furthermore, the present study analyzed the properties of the protein (IFNγ) dissolved in the above-mentioned solutions at low concentration.…”
Section: Introductionmentioning
confidence: 99%